EFEKTIVITAS PROGRAM LABORATORIUM BISNIS SANTRI DI PONDOK PESANTREN ANWARUL HUDA MALANG - Muhammad Syifa Zam Zami; Anggraeni, Ika Khusnia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The development of information and communication technology in the era of globalization has made Islamic boarding schools experience a paradigm shift from an institution that only focuses on deepening religious knowledge, but also becomes an institution for developing economic potential. One Islamic Boarding School already has a program to expand its economic potential is the Anwarul Huda Malang Islamic Boarding School. This research is here to reveal the extent to which the effectiveness of the students' economic empowerment program, especially the